Gender Differences In Giving Directions: A Case Study Of English Literature Students At Binus University - Sing, Tjoo Hong; Kalingga, Felicia Andrey (Bina Nusantara University, 2011)
Many researchers have said that there are differences in the ways people give direction between males and females, especially in spatial task (cardinal directions, topography, mileage, building, right/left markers) (e.g., Lawton, 2001; Dabbs et al., 1998). Here, the thesis investigates what differences occur between both genders in giving direction. The respondents are 25 females and 25 males of fifth semester Binus University students majoring in English Literature. The respondents answered with a certain route from Binus’s Anggrek Campus to Senayan City. The study was conducted by qualitative and quantitative method. From the data analysis, the writer discovered that gender does affect in selecting the key words in explaining direction it is found that there were differences in choosing key words in giving direction between females and males. The difference is women use more than twice spatial references than men do. In terms of verbal abilities, it was confirmed that female use longer explanation. However, in other aspects such as serial orientation and maintenance words, the result is inconclusive.